Environmental factors influencing the prevention of secondary health conditions among people with spinal cord injury, South Africa. - Sonti Pilusa (Public Library of Science (PLoS), 2021)
Background The environment where people live, work or play can influence health and disability outcomes. People with spinal cord injury are at risk for secondary health conditions, with this increasing readmission rates and decreasing quality of life. Studies on preventative care for secondary health conditions and factors influencing the prevention of secondary health conditions are scarce in low to middle-income countries. Aim To explore environmental factors influencing the prevention of secondary health conditions in people with spinal cord injury. Setting This study was based at a public rehabilitation hospital, South Africa. Methods Explorative qualitative design was used. Semi-structured interviews were conducted with 21 therapists, 17 people with a spinal cord injury and six caregivers. The interviews were transcribed verbatim. Analysis was conducted using content analysis. Results The categories that emerged included the impact of social support, inaccessible built environment and transport system, and an inefficient health care system. Sub-categories for the inefficient health care systems were: Shortage of resources, health workers lack of knowledge on prevention of secondary health conditions and inadequate patient care approach. Conclusion Environmental factors influencing the prevention of secondary health conditions are complex and multifactorial. When developing rehabilitation and prevention programmes, environmental factors must be considered.